(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the structure of the content of the pedagogical the practice o f the student’s — of future tutors I-II courses pedagogical university, direct on the formation of the readiness for the upbringing of responsibility in the preschool children’s.